9 - Book Reviews: John O. Hunwick, 2003, Arabic Literature of Africa Volume 4: The Writings of Western Sudanic of Africa. Leiden-Boston. Brill. 814p.: by Professeur Babacar Samb - journal system (Africa Development, 2022)
abstract